Structural response and continuous strength method design of slender stainless steel cross-sections. (1st June 2017) - Zhao, Ou; Afshan, Sheida; Gardner, Leroy
Highlights: Current codified design approaches for slender stainless steel cross-sections were briefly reviewed. The continuous strength method (CSM) has been extended to cover the design of slender stainless steel cross-sections. Assessment of the proposed CSM indicates a higher level of design accuracy and efficiency. The reliability of the new proposal has been confirmed by means of statistical analyses. Abstract: In current structural stainless steel design codes, local buckling is accounted for through a cross-section classification framework, which is based on an elastic, perfectly-plastic material model, providing consistency with the corresponding treatment of carbon steel cross-sections. Hence, for non-slender cross-sections, the codified design stress is limited to the 0.2% proof stress without considering the pronounced strain hardening exhibited by stainless steels, while for slender cross-sections, the effective width method is employed without considering the beneficial effect of element interaction. Previous comparisons between test results and codified predictions have generally indicated over-conservatism and scatter. This has prompted the development of more efficient design rules, which can reflect better the actual local buckling behaviour and nonlinear material response of stainless steel cross-sections. A deformation-based design approach called the continuous strength method (CSM) has been proposed for the design of stocky cross-sections, which relates the strength of a cross-section to its deformation capacity and employs a bi-linear (elastic, linear hardening) material model to account for strain hardening. In this paper, the scope of the CSM is extended to cover the design of slender stainless steel cross-sections under compression, bending and combined loading, underpinned by and validated against 794 experimental and numerical results. The proposed approach allows for the beneficial effect of element interaction within the cross-section, and is shown to yield a higher level of accuracy and consistency, as well as design efficiency, in the capacity predictions of slender stainless steel cross-sections, compared to the effective width methods employed in the current international design standards. Non-doubly symmetric sections in bending, which may be slender, but still benefit from strain hardening, are also discussed. The reliability of the CSM proposal has been confirmed by means of statistical analyses according to EN 1990, demonstrating its suitability for incorporation into future revisions of international design codes for stainless steel structures.